KAJIAN DESAIN INTERIOR BERNUANSA NATURAL-MODERN - Hajizah Azmi Siregar (Jurnal PATRA, 2021)
This research is motivated by the phenomenon of increasing modern life and is now becoming more active in arranging the interior by keeping up with the times. This is a challenge for architects and designers to come up with new and unique ideas. The interior concept of the khana spa is Natural Modern. Based on the character of the consumer, the location, and the times this concept suits khana spa. This research is descriptive qualitative research with a case study method. The analysis carried out is an analysis of the results of field observations and questionnaire survey data analysis. This research is expected to increase consumer comfort when in khana spa, supported by the growing level of consumer demand for the spa as a means of relaxation.